2016
DOI: 10.2169/internalmedicine.55.6082
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Endobronchial Ultrasound-guided Transbronchial Needle Aspiration in Patients with Small-cell Lung Cancer

Abstract: Objective Most small-cell lung cancers (SCLCs) are located within the central aspect of the chest and manifest as a mediastinal or hilar lymphadenopathy. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) makes it possible to perform mediastinal and hilar nodal examinations. The purpose of this study was to evaluate the performance of EBUS-TBNA in the diagnosis of SCLC. Methods The diagnostic performances of EBUS-TBNA and/or transesophageal bronchoscopic ultrasoundguided fine-needle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…1,2 Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has emerged as a useful technique for evaluating medaistinal/hilar lymphadenopathy since invented, including diagnosing and staging of lung cancer, diagnosis of mediastinal malignancies as well as some specific benign diseases, such as sarcoidosis and tuberculosis (TB), because it is a minimally invasive procedure that is generally available, easy to use and with minimal additional costs. [3][4][5][6][7][8][9] Less is known, however, about the utility of EBUS-TBNA for diagnosing non-specific intrathoracic inflammatory lymphadenopathy.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has emerged as a useful technique for evaluating medaistinal/hilar lymphadenopathy since invented, including diagnosing and staging of lung cancer, diagnosis of mediastinal malignancies as well as some specific benign diseases, such as sarcoidosis and tuberculosis (TB), because it is a minimally invasive procedure that is generally available, easy to use and with minimal additional costs. [3][4][5][6][7][8][9] Less is known, however, about the utility of EBUS-TBNA for diagnosing non-specific intrathoracic inflammatory lymphadenopathy.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, differentiating between inflammatory processes and malignancy is especially difficult and a pathological diagnosis is generally required. The overall sensitivity and specificity of EUS-FNA and/or endobronchial ultrasound (EBUS)-transbronchial needle aspiration were reported to be 97.4% and 100%, respectively [1]. Although severe complications are rare, we report 2 serious and life-threatening cases of esophageal wall rupture after EUS-FNA.…”
Section: Case Reportmentioning
confidence: 82%
“…The specificity may be too low to indicate usage of FDG-PET/CT alone as the staging method of SCLC compared to studies evaluating EBUS-TBNA indicating a higher specificity. 14 , 15 A recent study evaluated the benefits of increased incorporation of EBUS and PET/CT and indicated a more precise stratification. 16 The data suggest that FDG-PET/CT alone could not match up to that gain of stratification.…”
Section: Discussionmentioning
confidence: 99%